ENLIGHTENMENT IDEAS IN 18TH–19TH CENTURY AMERICAN AND UZBEK LITERATURE (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the ideas of Enlightenment that developed in the 18th–19th centuries in America and Central Asia, particularly in Uzbek literature. During this period, the concepts of science, education, moral reasoning, and social reform shaped the main intellectual currents. The article analyzes the emergence of Transcendentalism through the ideas of the European Enlightenment, as well as its interactions with the Jadid movement and their broader intellectual context.
Keywords: Enlightenment, Enlightenment Thought, Transcendentalism, Jadidism, American Literature, Uzbek Literature.